The expert expert witness : more maxims and guidelines for testifying in court - Brodsky, Stanley L., 1939-; Gutheil, Thomas G. (American Psychological Association, 2016)
"Psychologists, psychiatrists, and other mental health professionals may be experts in their respective fields, but this expertise does not easily translate to effective courtroom testimony. Even veteran expert witnesses can encounter new challenges in these high-pressure situations, especially during a cross-examination where every statement and gesture can be scrutinized by an attorney searching for ways to dispute the expert's credibility and opinions. For more than two decades, Stanley Brodsky has taught expert witnesses simple and practical strategies they can use to negotiate challenges in the courtroom and give strong, effective testimony. In this thorough update to his classic guide, Brodsky and his equally prolific coauthor, Thomas Gutheil, continue to provide sage, humorous advice that will put expert witnesses at ease and allow them to comport themselves with poise and confidence throughout direct and cross-examination. Short chapters punctuated by memorable maxims draw from the authors' expansive personal experiences, as well as research and stories from other expert expert witnesses, to create this must-have resource that will inform and entertain expert witnesses for many years"--Publicity materials. (PsycINFO Database Record (c) 2015 APA, all rights reserved).